A Retrospective Analysis of Peroperative Risk Factors Associated with Posttonsillectomy Reactionary Hemorrhage in a Teaching Hospital - Manimaran, Vinoth; Mohanty, Sanjeev; Jayagandhi, Satish Kumar; Umamaheshwaran, Preethi; Jeyabalakrishnan, Shivapriya (International Archives of Otorhinolaryngology, 2019)
Introduction Tonsillectomy is one of the most common otolaryngology procedures performed worldwide. It is also one of the first procedures learnt by residents during their training period. Although tonsillectomy is viewed relatively as a low-risk procedure, it can be potentially harmful because of the chance of posttonsillectomy hemorrhage.Objective The objective of the present study is to analyze the effects of peroperative factors and experience of the surgeon on the incidence and pattern of posttonsillectomy reactionary hemorrhage.Methods A retrospective review of medical charts was performed from 2014 to 2017 in a tertiary care hospital. A total of 1,284 patients who underwent tonsillectomy and adenoidectomy were included in the study. The parameters assessed were experience of the surgeon, operating time, intraoperative blood loss, difference in mean arterial pressure (MAP) and pulse rate.Results A total of 23 (1.79%) out of the 1,284 patients had reactionary hemorrhage. Out of those 23, 16 (69.5%) patients had been operated on by trainees, while 7 (30.5%) had been operated on by consultants (p = 0.033, odds ratio [OR] = 0.04). Operating time, intraoperative blood loss, difference in MAP and pulse rate were significantly higher in the reactionary hemorrhage group, and showed a positive association with risk of hemorrhage (p < 0.05; OR >1). Re-exploration to control the bleeding was required in 10 (76.9%) out of the 23 cases.Conclusion The experience of the surgeon experience and peroperative factors have an association with posttonsillectomy hemorrhage. Close surveillance and monitoring of the aforementioned peroperative factors will help in the identification of patients at risk of hemorrhage.
Keywords: tonsillectomy; reactionary hemorrhage; peroperative risk factors; hemorrhage